Resolution Efforts Land Dispute Through Mediation in Tanah Tengnga Village Subdistrict Palakka Bone Regency - Alwi Jaya; Tarmizi; Gustika Sandra (Publikasi Indonesia, 2022)
Counseling law as one form devotion to community at college tall own objective For educate and solve problem in society. In case This is counseling law implemented by the Pengayoman College of La Watampone related with problem dispute land frequently happened. Therefore that 's devotion This aim For add outlook public related effort solution dispute land through mediation as alternative solution dispute land in Tanah Tengnga Village Subdistrict Palakka Bone Regency. Method used in activity devotion This is counseling with give material technique mediation and simulation solution case dispute land, and ask answer. The result of activity This show that the people of Tanah Tengnga Village Subdistrict Palakka Bone Regency has more knowledge Good about mediation and methods solution dispute land through mediation. Activity This give significant and helpful benefits public in finish dispute land in a way deliberative and effective through mediation.